Tracking functional network connectivity dynamics in the elderly - Wu, Kaichao; Jelfs, Beth; Mahmoud, Seedahmed S.; Neville, Katrina; Fang, John Q. (Frontiers in Neuroscience, 2023)
Functional magnetic resonance imaging (fMRI) has shown that ageing disturbs healthy brain organization and functional connectivity. However, how this age-induced alteration impacts dynamic brain function interaction has not yet been fully investigated. Dynamic function network connectivity (DFNC) analysis can produce a brain representation based on the time-varying network connectivity changes, which can be further used to study the brain ageing mechanism for people at different age stages. Hence, this presented investigation examined the dynamic functional connectivity representation and its relationship with brain age for people at an elderly stage as well as in early adulthood. Specifically, the resting-state fMRI data from the University of North Carolina cohort of 34 young adults and 28 elderly participants were fed into a DFNC analysis pipeline. This DFNC pipeline forms an integrated dynamic functional connectivity (FC) analysis framework, which consists of brain functional network parcellation, dynamic FC feature extraction, and FC dynamics examination. The statistical analysis demonstrates that extensive dynamic connection changes in the elderly concerning the transient brain state and the method of functional interaction in the brain. In addition, various machine learning algorithms have been developed to verify the ability of dynamic FC features to distinguish the age stage. Results show that the fraction time of DFNC states has the highest performance, which can achieve a classification accuracy of over 88% by a decision tree. Furthermore, the dynamic FC alteration has been found to be correlated with mnemonic discrimination ability and could have an impact on the balance of functional integration and segregation.